Long-Term Growth following Trigonocephaly Repairs: Are Overcorrections Necessary?. Issue 3 (March 2020) - Fearon, Jeffrey A.; Ditthakasem, Kanlaya; Chan, Wing Nam J.; Herbert, Morley
Abstract : Background: Does bifrontal width change with growth following trigonocephaly corrections? Postoperative long-term growth was assessed, along with the impacts of phenotypic severity, surgical timing, and operative technique, to determine how wide to surgically set bifrontal width. Methods: A retrospective review of all trigonocephaly repairs was performed. Exclusion criteria included syndromic conditions, incomplete records, and follow-up under 1 year. Anthropometric measurements taken through completion of growth were evaluated and compared to sex- and age-matched normal standards for Z score conversion. Results: Of 370 consecutive patients undergoing repairs, 95 had sufficient anthropometric data. The mean surgical age was 10.8 months (range, 2 months to 7 years) and mean follow-up was 54.3 months (range, 12 months to 17.8 years). Sequential measurements revealed progressive increases in bifrontal width. However, following conversion to Z scores, the initial overcorrection (mean overcorrection, 8.7 mm; mean Z score, +2.3) steadily diminished to an undercorrection (mean measurement, −5.5 mm; mean Z score, −1.1). Compared to treatment at an older age (10 to 12 months), repairs performed in those younger than 8 months showed worse growth ( p = 0.004). Those more severely affected (lowest bifrontal Z scores) had growth similar to that of those more mildly impacted. Only two patients (2.1 percent) underwent secondary procedures for recurrences. No correlation was found between anthropologic measurements and observers' severity assessments. Conclusions: Subnormal bifrontal growth occurs following trigonocephaly corrections, especially with earlier corrections. Repairs performed at approximately 11 months of age had to be overcorrected by approximately 1.5 cm to produce a normal bifrontal width at maturity. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.